2005 Annual Conference Proceedings
DOI: 10.18260/1-2--14353
|View full text |Cite
|
Sign up to set email alerts
|

Effective Implementation Of Industry Sponsored Senior Design In A Civil Engineering Program

Abstract: The success of the industry-sponsored Civil Engineering senior design program at Stevens Institute of Technology and its impact on meeting the learning objectives established for the twosemester capstone design sequence is described. The effective use of industry sponsors to formally assess the student's performance will be presented as will the recruitment of sponsors. The dynamics of group size and structure will also be discussed. The information presented in this paper is based on the five years that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Capstone faculty view the course as a means to provide students with an opportunity to apply what they have learned throughout their undergraduate career through an open-ended design project in an environment that simulates the real world 13 . The benefit of the involvement of practicing engineering professionals has been discussed in the literature 14,15,16,17,18 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Capstone faculty view the course as a means to provide students with an opportunity to apply what they have learned throughout their undergraduate career through an open-ended design project in an environment that simulates the real world 13 . The benefit of the involvement of practicing engineering professionals has been discussed in the literature 14,15,16,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Brunell and Schaefer Jr 16 reported that the industry sponsors of the senior design program felt the time and money were well spent educating the engineers of the future, some of whom became their employees. They observed that the optimum group size of students was four with one of those being proficient in drawing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Design elements are typically incorporated across various courses. Examples of strategies used to help relate theory to practice include servicelearning projects, experiential-learning, case-based projects, and industry-based or industrysponsored projects 4,5,6,7,8,9 . The capstone design course is an integral part of the approach of many undergraduate CE programs.…”
Section: Introductionmentioning
confidence: 99%